Analysis of the winter and semiannual ionospheric anomalies in 1999?2009 based on GPS global International GNSS Service maps - Meza, A. (2012)
Our work is focused on the analysis of seasonal and semiannual ionospheric anomalies using vertical total electron content (VTEC) measurements obtained by the International GNSS Service (IGS). For this study we use principal component analysis (PCA) and wavelet transform (WT) because both numerical tools allow us to isolate principal components of the VTEC variability as much spatially as temporally. The IGS VTEC maps are reorganized, and from each daily global data set, two maps were constructed: one at 12:00 LT and the other at 22:00 LT. From these two series of VTEC maps covering the period 1999–2009 for each local time, we found that the semiannual anomaly is globally recorded at noon, especially at mid and low geomagnetic latitudes, and its amplitude has a close relationship with the solar activity, and at night this anomaly is recorded during high solar activity and the larger values are located in the South American region. The values of VTEC at the March equinox exceed that of the September equinox, especially during high solar activity; the winter anomaly is recorded at noon near the geomagnetic poles region, and the effect is more important during high solar activity. At night this anomaly is present during the ascending and descending phases and minimum of the solar cycle. Thus, the night winter anomaly effect is clearly evidenced from our results.